2019
DOI: 10.1038/s41591-019-0495-2
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with Akkermansia muciniphila in overweight and obese human volunteers: a proof-of-concept exploratory study

Abstract: Metabolic syndrome is characterized by a constellation of comorbidities that predispose individuals to an increased risk of developing cardiovascular pathologies as well as type 2 diabetes mellitus (T2DM)1. The gut microbiota is considered as a new key contributor involved in the onset of obesity-related disorders2. In humans, studies have provided evidence for a negative correlation between Akkermansia muciniphila abundance and overweight, obesity, untreated T2DM, or hypertension3–8. As the administration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

41
1,196
5
17

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,545 publications
(1,259 citation statements)
references
References 46 publications
41
1,196
5
17
Order By: Relevance
“…A recent clinical trial (NCT02637115) indicated that 3-month oral administration of A. muciniphila in obese patients is safe and well-tolerated. Meanwhile, supplementation of A. muciniphila decreased the body weight and improved liver dysfunction as well as inflammation in patients, as shown in a double-blind, randomized human study (Depommier et al, 2019). It has been demonstrated that A. muciniphila could be isolated from purified hog gastric mucus (Van Der Ark et al, 2018) and cultured in vivo for medicinal application.…”
Section: Resultsmentioning
confidence: 93%
“…A recent clinical trial (NCT02637115) indicated that 3-month oral administration of A. muciniphila in obese patients is safe and well-tolerated. Meanwhile, supplementation of A. muciniphila decreased the body weight and improved liver dysfunction as well as inflammation in patients, as shown in a double-blind, randomized human study (Depommier et al, 2019). It has been demonstrated that A. muciniphila could be isolated from purified hog gastric mucus (Van Der Ark et al, 2018) and cultured in vivo for medicinal application.…”
Section: Resultsmentioning
confidence: 93%
“…Such work demonstrated a ‘causal’ contribution of the microbiota to metabolism and has since lead to the isolation of bacterial species able to improve the metabolic disease. One such species is Akkermansia muciniphila, which is currently being assessed as a treatment for obesity …”
Section: Helminth Infection and Metabolic Statusmentioning
confidence: 99%
“…One such species is Akkermansia muciniphila, which is currently being assessed as a treatment for obesity. 74 Of note, intestinal helminths, such as N. brasiliensis, H. polygyrus or Trichuris muris, are directly at the intersection of type 2 immunity, microbiota and metabolism. These parasites all reside within the intestine as adults, where they are in close proximity to, and have co-evolved with, the microbiota (Figure 2).…”
Section: Possible Contribution Of Helminthmicrobiota Interactions Onmentioning
confidence: 99%
“…Additionally, members of the Lachnospiraceae and Erysipelotrichaceae families have previously been suggested to be associated with microbe TMA generation and development of atherosclerosis (Qiu, Tao, Xiong, Yu, & Wei, 2018). These species have been suggested as playing a role in inhibiting obesity as well as improving intestinal barrier function, possibly through interaction with host intestinal epithelial cells via mucoprotein(Berry et al, 2012;Depommier et al, 2019;Lee et al, 2018).The differences in the gut microbial species from different experimental groups were further defined using LEfSe analysis (Figure 4). The composition of the gut microbiota at the phylum and genus levels induced by the experimental diets is shown in Figure 3.…”
mentioning
confidence: 99%
“…without AMPK inhibition). These species have been suggested as playing a role in inhibiting obesity as well as improving intestinal barrier function, possibly through interaction with host intestinal epithelial cells via mucoprotein(Berry et al, 2012;Depommier et al, 2019;Lee et al, 2018).The differences in the gut microbial species from different experimental groups were further defined using LEfSe analysis (Figure 4). Species from Firmicutes phylum, Dubosiella, Chlamydia, Enterorhabdus, and Clostridium were identified to be significantly enriched in the mice fed with a red meat diet, potentially indicating a relatively unhealthy gut environment as these species have been associated with dysbiosis or pathogenicity (Kociolek & Gerding, 2016; Leclercq et al, 2017; Zhang et al, 2018).…”
mentioning
confidence: 99%